Draft Annual Plan 2006-07 Government of Punjab - Planning Commission (Planning Commission, 2006)
Punjab, is a predominantly an agricultural or rural economy. Out of the 66% rural population, nearly 80% population is still dependent on Agriculture and Allied Activities in the State. Stagnation in the agriculture production has already reached a plateau where no further increase in production is possible. the only solution to this problem is diversification of Agriculture and to reduce dependence on wheat -paddy rotation so that a shift is made towards medicinal plants, social forestry, the value added crops such as fruits, vegetables, flowers and dairy enterprise. Pulses and oil seeds also need to be encouraged to meet the shortage in the country.
Government of Punjab Department of Planning